1984
DOI: 10.2307/1129984
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Neurobehavioral Responses of Preterm Infants at Term Conceptional Age

Abstract: A revised Prechtl Neurological Examination was administered to 510 singleton infants at term conceptional age to assess the influence of gestational age, race, and sex on neurobehavioral responses in a "typical" newborn population. The infants were born at 1 of 5 centers and were subjects of the NIH Collaborative Study on Antenatal Steroid Therapy. Of these babies, 392 were born at less than 37 weeks gestational age, whereas 118 infants were born at greater than or equal to 37 weeks. Of a total of 50 items of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

1987
1987
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…4). Other studies have also reported neonatal gender differences for motility and sensorimotor behaviors, for example, low-intensity activity, patterns of activity development, and performance on neurological exams (Aylward et al, 1984;Buelke-Sam et al, 1984;Phillips et al, 1978). With advancing postnatal development from infant through adolescent ages, gender effects on motor behaviors are frequently reported (e.g., Aaron, Kriska, Dearwater, Anderson, Olsen, Cauley, & Laporte, 1993;Eaton & Enns, 1986;Gabriel, Chilla, & Kozielski, 1976;Johnson & Brody, 1977;Schwartz, Niman, & Gisel, 1984).…”
Section: Neonatal Movement Development: Birth To 6 Weeks Postnatalmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Other studies have also reported neonatal gender differences for motility and sensorimotor behaviors, for example, low-intensity activity, patterns of activity development, and performance on neurological exams (Aylward et al, 1984;Buelke-Sam et al, 1984;Phillips et al, 1978). With advancing postnatal development from infant through adolescent ages, gender effects on motor behaviors are frequently reported (e.g., Aaron, Kriska, Dearwater, Anderson, Olsen, Cauley, & Laporte, 1993;Eaton & Enns, 1986;Gabriel, Chilla, & Kozielski, 1976;Johnson & Brody, 1977;Schwartz, Niman, & Gisel, 1984).…”
Section: Neonatal Movement Development: Birth To 6 Weeks Postnatalmentioning
confidence: 99%
“…Gender differences have been reported for antenatal studies of hormones (Bayer et al, 1994;Hines, 1982;Meyer-Bahlburg et al, 1988;Reinisch, 1974;Toran-Allerand, 1984), nervous system (Beaston-Wimmer & Smolen, 1991;Engele, Pilgrim, & Reisert, 1989;Hutchison et al, 1994;de Lacoste et al, 1986;Patchev, Hayashi, Orikasa, & Almeida, 1995;Schindler, 1975), surfactant production and lung development (Hanley et al, 1996;Neilsen & Torday, 1981), biochemistry and immunology (Romero, Gomez, Galasso, Mazor, Berry, Quintero, & Cotton, 1994), and somatic growth (Ounsted et al, 1981, Scott, Guardian, Angelus, & Backstrom, 1991Sumulian et al, 1995). For newborn infants, there are reports of gender differences for motility and sensorimotor behaviors (Aylward et al, 1984;Buelke-Sam et al, 1984;Eaton & Enns, 1986;Phillips et al, 1978), as well as perinatal gender differences for the incidence of preterm birth (McGregor, Leff, Orleans, & Baron, 1992) and for perinatal mortality (Perelman, Palta, Kirby, & Farrell, 1986). The antenatal biological studies (particularly the hormonal, nervous system and growth studies) and the neonatal motor behavior studies converge to indicate that gender differences for antenatal movements might be expected, based on differential biological and behavioral developmental patterns for male and female fetuses and neonates.…”
Section: Fetal Movement Development: Gestational Age and Gender Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent touch may especially overload their neural apparatus, impeding their ability to process the myriad stimuli to which they are exposed. Less responsive infants with more complicated courses show both a diminished ability to modulate their arousal (Aylward et al, 1984) and substantial avoidance of interaction (Bennett, 1997) in an apparent attempt to manage their arousal. In addition, the painful probing and pricking experienced by very high risk infants in the course of their medical care may create some tactile aversion in these children which impedes their ability to effectively integrate tactile input later on (DeMaio-Feldman, 1994).…”
Section: Frequent Touch As a Risk Factormentioning
confidence: 99%
“…A mortalidade perinatal e a incidência de sequelas neurológicas em crianças prematuras têm diminuído, dados os avanços da perinatologia 5,6 . Mesmo as crianças de muito baixo peso ao nascer têm melhores chances de sobrevivência e estão menos sujeitas à elevada incidência de severas sequelas 5,7,8 .…”
unclassified